Still in search of strategic human resource management? A review and suggestions for future research with China as an example - Cooke, Fang Lee; Xiao, Mengtian; Chen, Yang (Human resource management, 2021)
Strategic human resource management (SHRM) has been an important strand of research in the HRM field for over three decades, and has attracted heated debates in recent years. One main critique of the state of SHRM research is its increasing detachment from HRM practice, in the pursuit of more theoretical rigor and methodological sophistication. Our review article has two main tasks. First, we review SHRM research published in two leading HRM journals—Human Resource Management and Human Resource Management Journal—in the light of the criticisms on SHRM research and use this as a backdrop of our second task. Second, we critically examine SHRM research conducted in the Chinese context by drawing on a systematic review on extant literature. In doing so, we draw on a wider range of HRM journals such as Human Resource Management Review, The International Journal of Human Resource Management, and so forth. We find that while the trend of psychologization in SHRM research is gathering pace, the range of theoretical perspectives mobilized to inform the studies is actually expanding. We call for SHRM research to be more contextualized and more practical phenomenon‐driven SHRM research. We indicate several avenues for future research, using China as an example.